Implementation of Smart City Program Policy on The Use of Samagov Application in Digital Sub-District of Samarinda Seberang - Lisdawati Lisdawati; Enos Paselle; Kus Indarto; Bambang Irawan (Poltanesa, 2025)
This research investigates the implementation of the Smart City program policy through the application of Samagov within the digital sub-district initiative in Samarinda Seberang. The study aims to examine the extent to which the policy has been realized in practice, as well as to identify the supporting and inhibiting factors influencing its effectiveness. Employing a qualitative descriptive approach, the data were collected through in-depth interviews, document analysis, and field observations. The research framework is grounded in George C. Edward III’s policy implementation model, which emphasizes four core variables: communication, resources, disposition of implementers, and bureaucratic structure. The findings reveal that although the application represents a strategic effort in modernizing public service delivery, several significant obstacles remain. These include ineffective communication between stakeholders, lack of clarity in information dissemination, insufficient trained human resources, and a bureaucratic structure that is not yet adaptive to digital transformation. Additionally, the supporting Standard Operating Procedures (SOPs) are still under development, which has led to inconsistencies in service execution. On the other hand, some enabling factors were identified, such as leadership commitment, availability of digital infrastructure, and collaboration with technology providers. The study concludes that a more structured and inclusive implementation strategy is needed, particularly by improving inter-agency coordination, simplifying SOPs, providing regular technical training, and increasing community digital literacy. The establishment of digital service units at the sub-district level is also recommended to ensure service consistency and accessibility. Effective policy implementation in this context is expected to accelerate digital governance practices and contribute to more transparent, efficient, and inclusive public service delivery in line with the Smart City vision.